Persepsi Khalayak pada Postingan Akun Instagram Publik Figure @Krisdayantilemos Terkait Penghapusan Syarat PCR dan Swab Antigen Pelaku Perjalanan Domestik - Anggraeny, Dwi Nuning; Tutiasri, Ririn Puspita; Achmad, Zainal Abidin; Zuhri4, Saifuddin (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Dwi Nuning Anggraeny1, Ririn Puspita Tutiasri2, 3, 1-4Program Studi Ilmu Komunikasi, UPN “Veteran” Jawa Timur dwinuninganggraeni2@gmail.com ABSTRACT This study aims to find out how the public perceives the posting of the Instagram Public Figure @Krisdayantilemos Account regarding SE Regulation Number 22 of 2022 Regarding the Elimination of PCR Requirements and Antigen Swabs for Domestic Travel Users. Social media has become a good medium during the current Covid-19 pandemic, as a means of sharing information and policies related to Covid-19. The availability of information on digital technology, especially on Instagram social media, greatly influences the formation of public perceptions. The method used in this study is a qualitative descriptive method that aims to explain certain phenomena clearly and in detail. By conducting interviews through the personal Instagram of the informants. Based on the results of research conducted using 7 informants who knew and commented on posts from Instagram @krisdayantilemos, who posted that Krisdayanti disagreed regarding the abolition of PCR requirements and antigen swabs for domestic travel users. Information regarding Krisdayanti's disapproval of domestic travel regulations without antigen and PCR swab tests on the Instagram social media account @krisdayantileos gave rise to various perceptions from the large number of audiences who gave pros and cons of Krisdayant's posts. Keywords: Perception, The Latest Domestic Travel Regulations, Audience, Instagram